Pengaruh kompetensi, motivasi, lingkungan kerja dan persepsi gaya kepemimpinan terhadap kinerja penyuluh keluarga berencana - Nur Dwi Pujiyanto; Dyah Retna Puspita; Bambang Tri Harsanto (Faculty of Social and Political Science, Universitas Airlangga, 2017)
Nowadays the Family Planning Extension (PKB) still plays crucial role in supporting the success of population programs and family development. The implementation of decentralization policies that impacting existence of family planning programs is interesting for further analysis in their relation to the performance of PKB. In Kabupaten Pemalang, their performance is still relatively good. This good performance due to a number of factors such as competence, work motivation, work environment and leadership style perception. This study aims to examine to what extent the influence of four variables on the performance of PKB as a single or common variables. The research used a quantitative approach. Research populations are PKB members which consist of 93 people, all of which are sampled (total sample technique). Data obtained through questionnaires which then analyzed using simple linear regression test and multiple linear regression with the help of SPSS version 20 program. The results showed there is a significant influence of competence on PKB performance of 44.7 percent. Similarly, the work motivation, work environment and perceptions of the leadership style of supervisors individually influence the performance of PKB respectively by 15.3 percent, 39.7 percent and 18.4 percent. These four variables also affect the performance of PKB of 52.8 percent. The research concluded that the effort to improve the performance of PKB in Pemalang Regency is by increasing the competence of PKB through education and training activities, support facilities and work infrastructure and execution of tasks democratic. Another effort is to provide encouragement and appreciation.